Improved algorithm for engineering calculations of the parameters of a container tipping mechanism in a garbage truck taking into account the wear of friction pairs - Bereziuk, O.V.; Savulyak, V.I.; Kharzhevskyi, V.O.; Ivanov, S. Cv.; Yavorskyi, V.Ye. (Problems of Tribology, 2026)
The article is dedicated to the development of the scientifically grounded improved method, based on the analysis of scientific literature sources, for the design calculation of the parameters of a mechanism for tipping a container with municipal solid waste into a garbage truck, taking into account friction wear, in order to determine its main geometric, force, and speed parameters. The drive of the working parts of the mechanism for tipping a container with municipal solid waste into a garbage truck is hydraulic, with a power source from the garbage truck’s pump station. The usage of the proposed improved methodology for the engineering calculation of the parameters of the mechanism for tipping a container with municipal solid waste into a garbage truck, taking into account the wear of friction pairs, allows significant reduction in design time and avoids unnecessary costs for labor-intensive experimental and theoretical research. Using the proposed scientifically based improved method of design calculation of the parameters of the mechanism for tipping a container with municipal solid waste into a garbage truck, taking into account the wear of friction pairs, its main geometric, force, and speed parameters have been determined. It has been established that the development of an improved methodology for the design calculation of the parameters of the mechanism for rotating the manipulator lever during the loading of municipal solid waste into a garbage truck, taking into account the wear of friction pairs, requires further research